(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2026)
In the current conditions of globalization and economic integration, improving the mechanism for forming local budget revenues in Uzbekistan is considered a key factor in ensuring regional financial independence and promoting sustainable socio-economic development. This article provides a deep analysis of the existing problems of fiscal centralization and proposes ways to expand the tax base, optimize the transfer system, and introduce digital management elements based on international experience. The research findings contribute to reducing fiscal imbalances between regions by increasing the financial responsibility of local authorities and enhancing the overall efficiency of the state financial system.